EFFECTIVENESS OF CEREBROLYSIN IN THE TREATMENT OF ENCEPHALOPATHY IN CHRONIC KIDNEY DISEASE - Dilbar I. Rakhmatova (Central Asian Journal of Medicine, 2024)
54 patients were examined with encephalopathy in chronic kidney disease. They were undergone clinic-instrumental and neuropsychologic examination. In comprasion with Cerebrolysin at the dose of 20 ml and 30 ml, 30 ml dose of Cerebrolysin effected positively to intellectual-mnestic disorders, by developing its neuroprotective action. In addition, at this dose of drug, brain bioelectrical activity were improved faster in EEG.